Pengaruh social media marketing, product quality, dan store atmosphere terhadap purchase intention dengan brand image sebagai variabel mediasi pada coffee shop di Aceh - Soefhwan, Soefhwan; Kurniawati, Kurniawati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research aims to find out and analyze the influence of social media marketing, product quality and store atmosphere on brand image and the influence of social media marketing, product quality, store atmosphere and brand image on purchase intentions at coffee shops in Aceh. The study sample used 210 respondents selected with the criteria of having visited a Coffee Shop in Aceh at least 2 times. The method used in this study is causality research. The results showed that partially social media marketing, product quality and store atmosphere had a positive and significant effect on the brand image of coffee shops in Aceh. Partially social media marketing, product quality, store atmosphere and brand image have a positive and significant effect on purchase intentions at coffee shops in Aceh. Brand image can mediate the relationship of influence between social media marketing, product quality and store atmosphere with purchase intention..